Seed emergence and growth of the short age sugar palm (Arenga pinnata) as a response of seed scarification and liquid organic fertilizer application - ELIDAR, YETTI (Asian Journal of Agriculture, 2018)
Elidar Y. 2018. Seed emergence and growth of the short age sugar palm (Arenga pinnata) as a response of seed scarification and liquid organic fertilizer application. Asian J Agric 2: 8-13. The research was aimed to know the effect of seed scarification and liquid organic fertilizer application to the seed emergence and growth of the short age sugar palm (Arenga pinnata (Wurmb.) Merr). The research was conducted at two experiments, i.e. (i) effect of seed scarification, and (ii) effect of liquid organic fertilizer application. The first experiment was a single factor designed at Completely Randomized Design (CRD). The factor consisted of 4 scarification technique treatments i.e. s1 = seed abaxial scarification; s1 = seed tip scarification; s3 = seed left and right sides scarification; s4= seed embryo scarification. All treatments were replicated 6 times. The second experiment was arranged at a factorial (3 x 3) using Completely Randomized Design (CRD) with 6 replications. The first factor was the dose/volume of liquid organic fertilizer treatment in concentration of 3 cc L-1 of water (D) consisting of 3 levels i.e. d1 = 300 mL; d2 = 400 mL; d3 = 500 mL, while the second treatment was the interval of liquid organic fertilizer (I) application consisting of 3 levels i.e. i1 = 2 weeks; i2 = 3 weeks; i3 = 4 weeks. Seedling emergence test, germination rate, vigor index and seed germination percentage were measured and the growth parameters such as the plant height increase, plant midrib girth, number of midrib increase, and number of leaves were observed. The results showed that scarification at the embryo part (s4) resulted in the best seed germination percentage of the short age sugar palm at around 99.81%. Combination treatments between 500 mL dose of liquid organic fertilizer in concentration of 3 cc L-1 of water with the interval of 2 weeks (d3i1) produced the best seedling growth of the short age sugar palm.